OPTIMIZATION OF PERSONAL TAXATION - N. Beskorovaynaya; N. Marchenko (Вестник Северо-Кавказского федерального университета, 2022)
The low growth rate of welfare and consumer spending of the population exacerbated the problem ofjustifying the tax burden on individuals and forming an adequate tax mechanism for the redistribution of income. The analysis showed a relative increase in tax payments in recent years, with a decrease in real disposable income. The article shows the schedule of payments of basic taxes for quintile groups of the population depending on the size of income. The conclusion that it is necessary to introduce a progressive scale of tax on income and reduce the burden on the value-added tax is justified.